Current collector for battery, electrode for battery, method for manufacturing current collector for battery, and method for manufacturing electrode for battery
A battery current collector with a primer coat layer of crystalline resin and carbon particles addresses the weak adhesion issue in existing methods, enhancing adhesion strength and reducing internal resistance.
Patent Information
- Application Number
- JP2024086449
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-30
- Filing Date
- 2024-05-28
- Publication Date
- 2025-01-20
AI Technical Summary
Existing methods for manufacturing battery electrodes, whether through coating or hot pressing, result in weak adhesion of the electrode active material layer to the current collector, leading to increased interfacial resistance and potential peeling, which affects battery performance.
A battery current collector with a conductor layer and a primer coat layer composed of a mixture of crystalline resin and carbon particles, where the crystalline resin has a melting point of 200°C or less, enhances the adhesion strength of the electrode active material layer.
The proposed solution increases the adhesion strength of the electrode active material layer to the current collector, reducing internal resistance and preventing peeling, thereby improving battery performance.
Smart Images

Figure 2025009872000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a current collector for a battery, an electrode for a battery, a method for manufacturing a current collector for a battery, and a method for manufacturing an electrode for a battery. [Background technology]
[0002] Electrodes contained in lithium ion batteries and the like are usually manufactured by coating a current collector with a slurry in which an electrode active material is dispersed in an organic solvent in which a binder is dissolved, and then drying the coating film. However, there is a problem in that a large amount of CO2 emissions are generated because a large amount of energy is used to dry the coating film. As a method other than coating, a method of fixing an electrode active material layer to a current collector by hot pressing is known (for example, see Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-36508 Summary of the Invention [Problem to be solved by the invention]
[0004] However, in the method of fixing the electrode active material layer to the current collector by hot pressing, the adhesion of the electrode active material layer to the current collector may be weak. If the adhesion is weak, the interfacial resistance between the electrode active material layer and the current collector may increase, leading to an increase in the internal resistance of the battery, and the electrode active material layer may peel off and be detached from the current collector. On the other hand, even when the electrode active material layer is formed on the current collector by using a coating method, the adhesion of the electrode active material layer to the current collector may be weak. The present invention has been made in view of the above circumstances, and provides a current collector for a battery that can increase the adhesive strength of an electrode active material layer to the current collector. [Means for solving the problem]
[0005] The present invention provides a coating material for a conductive film, the coating material comprising a conductive layer and a primer coat layer provided on the conductive layer, the primer coat layer being a mixture layer of a crystalline resin and carbon particles, the mass of the primer coat layer per unit area being 0.1 g / m 2 More than 5g / m 2 and the melting point of the crystalline resin contained in the primer coat layer is 200° C. or lower. Effect of the Invention
[0006] By using the battery current collector of the present invention, the adhesive strength of the electrode active material layer to the current collector can be increased. This has become evident from experiments carried out by the inventors of the present application. [Brief description of the drawings]
[0007] [Figure 1] 1 is a schematic cross-sectional view of a current collector for a battery according to one embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view of a battery electrode according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, a number of embodiments of the present invention will be described with reference to the drawings. The configurations shown in the drawings and the following description are merely examples, and the scope of the present invention is not limited to those shown in the drawings and the following description.
[0009] FIG. 1 is a schematic cross-sectional view of a battery current collector according to this embodiment, and FIG. 2 is a schematic cross-sectional view of a battery electrode according to this embodiment. The battery current collector 10 of this embodiment includes a conductive layer 2 and a primer coat layer 3 provided on the conductive layer 2. The primer coat layer 3 is a mixture layer of a crystalline resin and carbon particles. The mass of the primer coat layer 3 per unit area is 0.1 g / m. 2 More than 5g / m 2 The melting point of the crystalline resin contained in the primer coat layer 3 is smaller than that of the primer coat layer 3, and is 200° C. or lower. The battery electrode 20 of this embodiment includes the battery current collector 10 of this embodiment and an electrode active material layer 5 provided on the primer coat layer 3.
[0010] The battery current collector 10 is a current collector for a battery electrode, and serves as a conductive path between the electrode active material layer 5 and a battery terminal. The battery is not particularly limited, but is preferably a lithium ion battery. The battery current collector 10 may be used for the positive electrode of the battery, or may be used for the negative electrode of the battery. The battery current collector 10 may be a current collector for collecting positive or negative charges from the electrode active material layer 5.
[0011] The conductive layer 2 is a main component of the battery current collector 10, and serves as a conductive path between the electrode active material layer 5 and the battery terminal. The conductive layer 2 is, for example, a metal foil, more specifically, an aluminum foil, a copper foil, a stainless steel foil, a nickel foil, or the like. The conductive layer 2 may be subjected to a corona discharge treatment before the formation of the primer coat layer 3. This can improve the hydrophilicity of the surface of the conductive layer 2, and an aqueous dispersion medium can be used in the formation of the primer coat layer 3.
[0012] The primer coating layer 3 is a layer provided on the conductor layer 2. In the battery electrode 20, the primer coating layer 3 is located between the conductor layer 2 and the electrode active material layer 5. The primer coating layer 3 is a mixture layer of a crystalline resin having a melting point of 200° C. or less and carbon particles. The carbon particles contained in the primer coating layer 3 serve as a conductive path between the conductive layer 2 and the electrode active material layer 5. This makes it possible to prevent the electrical resistance between the conductive layer 2 and the electrode active material layer 5 from becoming high.
[0013] The carbon particles contained in the primer coat layer 3 are, for example, conductive materials such as graphite particles, carbon black, carbon nanotubes, graphene, etc., and mixtures of two or more of these. The average particle size D50 of the carbon particles contained in the primer coat layer 3 is, for example, 50 μm or less, preferably 30 μm or less, and more preferably 20 μm or less.
[0014] The crystalline resin (crystalline polymer) contained in the primer coat layer 3 functions as a binder for the primer coat layer 3. The crystalline resin (crystalline polymer) is a polymer having crystallinity, and has a glass transition temperature and a melting point. The melting point of the crystalline resin contained in the primer coat layer 3 is 200°C or lower. The melting point of the crystalline resin contained in the primer coat layer 3 may be 180°C or lower, or may be 160°C or lower.
[0015] The crystalline resin contained in the primer coating layer 3 is, for example, a polyolefin, specifically, polyethylene, polypropylene, an ethylene-propylene copolymer, etc. Furthermore, the primer coating layer 3 may contain a mixture of at least two of these resins. The size or thickness of the crystalline resin in the primer coating layer 3 is from 0.01 μm to 40 μm, preferably from 0.01 μm to 30 μm, and more preferably from 0.01 μm to 20 μm.
[0016] The crystalline resin contained in the primer coat layer 3 may be a resin derived from an emulsion in which crystalline resin particles are dispersed in an aqueous dispersion medium. Since the crystalline resin particles contained in the emulsion have a small particle size, the primer coat layer 3 can be made homogenous. The crystalline resin contained in the primer coating layer 3 may be a resin derived from a powder of a crystalline resin.
[0017] The primer coat layer 3 can contain 100 parts by mass or more and 1000 parts by mass or less of carbon particles relative to 100 parts by mass of the crystalline resin, preferably 120 parts by mass or more and 800 parts by mass or less of carbon particles, and more preferably 130 parts by mass or more and 500 parts by mass or less of carbon particles. When the primer coat layer 3 contains carbon particles, it is possible to suppress an increase in the internal resistance of the battery electrode 20.
[0018] The mass (weight) of the primer coat layer 3 per unit area is 0.1 g / m 2 More than 5g / m 2 Smaller, preferably 0.3 g / m 2 More than 4.0g / m 2 less than 0.5 g / m 2 More than 3.0g / m 2 The mass of the primer coating layer 3 is 0.1 g / m 2 By setting the mass of the primer coat layer 3 to 5 g / m or more, the adhesive strength of the electrode active material layer 5 to the conductor layer 2 can be increased. 2 By making it smaller, the internal resistance of the battery electrode 20 can be prevented from increasing. The primer coating layer 3 may be a layer having a substantially uniform thickness. The primer coating layer 3 may be provided so that substantially the entire surface of the primer coating layer 3 on the conductive layer side is in contact with the conductive layer 2.
[0019] The primer coat layer 3 can be formed, for example, by applying a dispersion liquid (primer coat layer coating liquid) in which crystalline resin particles and carbon particles are dispersed in a dispersion medium onto the conductive layer 2, and drying the applied film. The method for applying the primer coat layer coating liquid onto the conductive layer 2 is not particularly limited, but may be, for example, a gravure coating method.
[0020] The dispersion medium of the primer coat layer coating liquid (dispersion liquid) may be water, may be an aqueous dispersion medium containing water and a water-soluble organic compound, or may be a dispersion medium containing water and a liquid organic compound. By including a water-soluble organic compound or a liquid organic compound in the primer coat layer coating liquid, the crystalline resin particles can be suppressed from aggregating, and the homogeneity of the primer coat layer 3 can be improved. This makes it possible to increase the adhesion strength of the electrode active material layer 5 to the conductor layer 2. The water-soluble organic compound or the liquid organic compound may be an organic compound having a boiling point of 70°C or higher, an organic compound having a boiling point of 100°C or higher, an organic compound having a boiling point of 130°C or higher, an organic compound having a boiling point of 150°C or higher, or an organic compound having a boiling point of 180°C or higher.
[0021] Examples of the water-soluble organic compound or liquid organic compound contained in the coating liquid for the primer coat layer include isopropyl alcohol, dipropylene glycol monomethyl ether, diethylene glycol monomethyl ether, methylcyclohexane, ethyl acetate, N-methyl-2-pyrrolidone (NMP), cyclohexanone, tetrahydronaphthalene, normal-dodecane, etc. The coating liquid for the primer coat layer may contain two or more of these organic compounds. The proportion of the organic compound in the coating liquid for the primer coat layer is, for example, 0.5 to 85 mass percent, preferably 0.5 to 55 mass percent, and more preferably 1.0 to 35 mass percent.
[0022] The crystalline resin contained in the coating liquid for the primer coat layer may be a resin derived from an emulsion in which crystalline resin particles are dispersed in an aqueous dispersion medium. Also, the crystalline resin contained in the coating liquid for the primer coat layer may be a resin derived from a powder of the crystalline resin. The carbon particles contained in the coating liquid for the primer coat layer are, for example, conductive materials such as graphite particles, carbon black, carbon nanotubes, and graphene. The coating liquid for the primer coat layer may contain two or more types of carbon particles selected from these.
[0023] The electrode active material layer 5 (electrode active material layer 5 included in the battery electrode 20) formed on the primer coat layer 3 may be a positive electrode active material layer or a negative electrode active material layer. The electrode active material layer 5 may have porosity and may contain electrode active material particles and a binder. Furthermore, the electrode active material layer 5 may contain a conductive material as necessary. Furthermore, the electrode active material layer 5 may be a layer containing both an electrode active material and a solid electrolyte (electrode active material layer for an all-solid-state battery). In the case of a positive electrode of a lithium ion battery, the electrode active material is, for example, lithium nickel cobalt manganese oxide, lithium iron phosphate, etc. The average particle size of the electrode active material particles is, for example, 0.1 μm or more and 50 μm or less.
[0024] The electrode active material layer 5 may be a dried coating film formed by applying a paste for the electrode active material layer. The electrode active material layer 5 may be bonded to the current collector 10 by pressing the electrode active material layer 5 against the current collector 10 (for example, a battery electrode produced by a dry process, an electrode for an all-solid-state battery, etc.). In this case, the manufacturing method for the battery electrode 20 may include a step of bonding the current collector 10 and the electrode active material layer by pressing the electrode active material layer 5 against the current collector 10. This bonding step may be performed at a temperature of 80°C or higher and 200°C or lower, and is preferably performed at a temperature of 80°C or higher and 180°C or lower. The bonding step may be performed at a temperature of 80°C or higher and higher than the melting point of the crystalline resin contained in the primer coat layer 3.
[0025] Preparation of battery cathodes and lithium-ion batteries Positive electrodes for batteries and lithium ion batteries were produced in Examples 1 to 3 and Comparative Examples 1 to 3. Table 1 shows the composition of the paint (listed in parts by mass) used to produce the primer coat layer of the positive electrode contained in each lithium ion battery, and the mass (weight per unit area) of the primer coat layer.
[0026] [Table 1]
[0027] [Example 1] A primer coat layer paint was prepared by mixing 500 parts by mass of water, 300 parts by mass of diethylene glycol monomethyl ether, 150 parts by mass of carbon particles (graphite particles + carbon black), and 100 parts by mass of aqueous polyethylene emulsion (solid content concentration: 30 wt%). The mass (weight) of the primer coat layer per unit area was 1.0 g / m 2 The primer coat layer paint was applied to the corona discharge-treated aluminum foil by gravure coating so that the primer coat layer was formed by drying the applied film, thereby producing the current collector of Example 1.
[0028] A positive electrode active material, lithium nickel cobalt manganese oxide (ternary system NCM811, average particle size 10 μm), was mixed with a binder and a solvent to prepare a positive electrode active material paste, which was then passed through a roll and dried to prepare a positive electrode active material sheet. The prepared positive electrode active material sheet was placed on the primer coat layer of the current collector of Example 1, and rolled with a roll laminator to prepare the battery positive electrode of Example 1. The conditions for roll lamination were a linear pressure of 34 kg / cm and a temperature of 100°C.
[0029] A negative electrode active material paste was prepared by mixing graphite particles, which were a negative electrode active material, with an aqueous dispersion medium, and the negative electrode active material paste was applied onto a copper foil and dried to form a negative electrode active material layer. In this manner, a battery negative electrode was produced. The coin-type lithium ion battery of Example 1 was produced using the battery positive electrode of Example 1, the produced battery negative electrode, a separator, and an electrolyte.
[0030] [Example 2] A battery positive electrode and a lithium ion battery of Example 2 were produced in the same manner as the battery positive electrode and the lithium ion battery of Example 1, except that a paint for a primer coating layer was prepared by mixing 800 parts by mass of water, 150 parts by mass of carbon particles (graphite particles + carbon black), and 100 parts by mass of an aqueous polyethylene emulsion (solid content concentration: 30 wt%).
[0031] [Example 3] The battery positive electrode and lithium ion battery of Example 3 were produced in the same manner as the battery positive electrode and lithium ion battery of Example 1, except that a paint for the primer coating layer was prepared by mixing 800 parts by mass of water, 150 parts by mass of carbon particles (graphite particles + carbon black), and 100 parts by mass of polyethylene particles (average particle size: about 10 μm).
[0032] [Comparative Example 1] In forming the primer coat layer, the mass (weight) of the primer coat layer per unit area is 5.0 g / m 2 A battery positive electrode and a lithium ion battery of Comparative Example 1 were produced in the same manner as the battery positive electrode and the lithium ion battery of Example 1, except that the primer coating layer paint was applied by gravure coating onto an aluminum foil that had been subjected to a corona discharge treatment so that the battery positive electrode and the lithium ion battery of Comparative Example 1 were produced.
[0033] [Comparative Example 2] A battery positive electrode and a lithium ion battery of Comparative Example 2 were produced in the same manner as the battery positive electrode and the lithium ion battery of Example 1, except that a paint for a primer coat layer was prepared by mixing 800 parts by mass of water, 150 parts by mass of carbon particles (graphite particles + carbon black), and 100 parts by mass of an aqueous acrylic emulsion (solid content concentration: 40 wt%).
[0034] [Comparative Example 3] A battery positive electrode and a lithium ion battery of Comparative Example 3 were produced in the same manner as the battery positive electrode and the lithium ion battery of Example 1, except that 800 parts by mass of water, 150 parts by mass of carbon particles (graphite particles + carbon black), and 100 parts by mass of carboxymethyl cellulose (CMC) were mixed to prepare a paint for the primer coating layer.
[0035] Peel Strength Test Peel strength was measured using a 180-degree peel strength tester, and the adhesive strength between the aluminum foil and the positive electrode active material sheet included in the battery positive electrodes of Examples 1 to 3 and Comparative Examples 1 to 3 was evaluated. The evaluation results are shown in Table 1. In Table 1, battery positive electrodes in which the adhesive strength between the aluminum foil and the positive electrode active material sheet was large and the positive electrode active material sheet was torn during the peel strength test were evaluated as "◎", battery electrodes in which the peel strength was 0.4 N / cm or more were evaluated as "◯", and battery electrodes in which the peel strength was less than 0.4 N / cm were evaluated as "×".
[0036] The adhesive strength of the battery electrodes in Examples 1 to 3 and Comparative Example 1, in which the primer coat layer contained polyethylene, was evaluated as "◎" or "◯", whereas the adhesive strength of the battery electrode in Comparative Example 2, in which the primer coat layer contained acrylic resin, and the adhesive strength of the battery electrode in Comparative Example 3, in which the primer coat layer contained CMC, were evaluated as "×". This shows that the adhesive strength of the positive electrode active material sheet to the current collector can be increased by including polyethylene in the primer coat layer.
[0037] The battery electrodes of Example 1 and Comparative Example 1, which include a primer coat layer prepared using a primer coat layer paint containing a water-soluble organic compound, diethylene glycol monomethyl ether, and water, were evaluated for adhesion strength as "◎", whereas the battery electrodes of Examples 2 and 3, which include a primer coat layer prepared using a primer coat layer paint not containing diethylene glycol monomethyl ether, were evaluated for adhesion strength as "◯". This shows that the adhesion strength of the positive electrode active material sheet to the current collector can be increased by forming a primer coat layer using a primer coat layer paint containing a water-soluble organic compound and water.
[0038] Charge / discharge cycle test The lithium ion batteries of Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to 100 charge / discharge cycles, and the charge / discharge cycle characteristics of each lithium ion battery were evaluated. The evaluation results are shown in Table 1. In Table 1, lithium ion batteries whose charge / discharge efficiency at the 100th cycle was 80% or higher are evaluated as "◯", and lithium ion batteries whose charge / discharge efficiency at the 100th cycle was 80% or lower are evaluated as "X". The lithium ion batteries of Examples 1 to 3 and Comparative Examples 2 and 3 were evaluated as "good," indicating that these batteries had high charge / discharge efficiency. The lithium ion battery of Comparative Example 1 was evaluated as "X". This is believed to be because the mass of the primer coating layer per unit area was large and the density of the polyethylene particles was high, resulting in high internal resistance of the positive electrode. [Explanation of symbols]
[0039] 2: Conductive layer 3: Primer coat layer 5: Electrode active material layer 10: Battery current collector 20: Battery electrode
Claims
1. A conductive layer and a primer coat layer provided on the conductive layer, the primer coat layer is a mixture layer of a crystalline resin and carbon particles, The mass of the primer coating layer per unit area is 0.1 g / m 2 5g / m or more 2 Smaller, A current collector for a battery, wherein the melting point of the crystalline resin contained in the primer coat layer is 200° C. or lower.
2. 2 . The battery current collector according to claim 1 , wherein the primer coating layer contains 100 parts by mass or more and 1,000 parts by mass or less of carbon particles with respect to 100 parts by mass of the crystalline resin.
3. 2 . The battery current collector according to claim 1 , wherein the primer coating layer is provided such that substantially the entire surface of the primer coating layer facing the conductive layer is in contact with the conductive layer.
4. The battery current collector according to claim 1 , wherein the conductive layer is a metal foil.
5. 2. The battery current collector according to claim 1, wherein the crystalline resin contained in the primer coat layer is a polyolefin.
6. 6. A battery electrode comprising the current collector according to claim 1 and an electrode active material layer provided on the primer coat layer.
7. A method for manufacturing a battery current collector, comprising the steps of applying a dispersion liquid, in which crystalline resin particles and carbon particles are dispersed in a dispersion medium containing a water-soluble organic compound or a liquid organic compound and water, onto a conductive layer, and drying the applied film to form a primer coat layer.
8. The method according to claim 7 , wherein the crystalline resin particles contained in the dispersion are resin particles derived from an emulsion.
9. A method for manufacturing a battery electrode, comprising a joining step of pressing an electrode active material layer against the current collector according to any one of claims 1 to 5 to join the current collector and the electrode active material layer.
10. The method according to claim 9 , wherein the bonding step is performed at a temperature of 80° C. to 200° C.
Citation Information
Patent Citations
Active material composite, electrode, power storage device and method for manufacturing active material composite
JP2021036508A